'Ozen', the First Spring Hulless Barley Cultivar in Turkey. Issue 3 (3rd August 2017) - Ergun, Namuk; Sayim, Ismail; Aydogan, Sinan; Tekin, Mehmet; Sanal, Turgay; Akar, Taner
Abstract : 'Ozen' (Reg. No. CV‐363, PI 682088), the first two‐rowed spring hulless barley ( Hordeum vulgare L.) cultivar developed in Turkey, was released and registered by the Central Research Institute for Field Crops, Ankara, Turkey, in 2012. The parents of Ozen are ICB‐101086 and 'Tokak 157/37'; it was selected by modified bulk selection method from the F2 to F7 generations. On the basis of yield, quality, and disease resistance data from preliminary yield, yield, and regional yield trials, Ozen was nominated to continue to registration trials in 2009. It was tested in four different locations during the registration trials under supplementary irrigation in the Central Anatolia and Transitional Zones by the Variety Registration and Seed Certification Center. Its mean grain yield increased from 2.755 kg ha −1 in 2010 to 3.784 kg ha −1 in 2011. The test weight of Ozen (76.2 kg L −1 ) was higher than other checks, and its 1000 kernel weight (35.2 g), protein ratio (14.3%), plant height (83.9 cm), and heading date (70.4 d) were close to the grand mean of the other checks. Ozen was developed mainly to be blended with wheat ( Triticum aestivum L.) flour at a given percentage without any negative effect on bread properties, while increasing the digestibility of bread. A study showed that 20% Ozen flour can be blended with wheat flour with the intended results, leading the bread industry in Turkey to recently produce the first bread consisting of 20% barley flour using Ozen.